1993
DOI: 10.1007/bf00043940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of media for their aptitude in wheat anther culture

Abstract: Different media were evaluated with anthers of five spring wheat (Triticum aestivum L.) genotypes for their ability to produce embryos and green plants in anther culture. Our first experiment showed that the addition of a combination of 19 amino acids significantly increased the number of embryos and green plants obtained. The mean number of green plants per 100 anthers for the two genotypes in this experiment, HY320 and B723, went from 28.2 without amino acids in the medium, to 46.7 with addition of amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…Addition of a combination of amino acids (arginine, aspargine, cystine, glutamine, glycine and proline; 1.0 and 2.0 mM) to the induction medium was beneficial in induction of embryos (Table 1). Addition of a combination of amino acids has also been beneficial for induction of embryos and plantlet regeneration in Cucumis sativus (Ashok , Hordeum vulgare (Ouédraogo et al 1998), Triticum aestivum (Trottier et al 1993), and Zea mays (Claparols et al 1993). Embryo induction was also improved with the addition of putrescine and spermidine (5, 10, 50, 100, 200, 500, 1000 μM) to the induction medium compared to the control (Table 2).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 87%
“…Addition of a combination of amino acids (arginine, aspargine, cystine, glutamine, glycine and proline; 1.0 and 2.0 mM) to the induction medium was beneficial in induction of embryos (Table 1). Addition of a combination of amino acids has also been beneficial for induction of embryos and plantlet regeneration in Cucumis sativus (Ashok , Hordeum vulgare (Ouédraogo et al 1998), Triticum aestivum (Trottier et al 1993), and Zea mays (Claparols et al 1993). Embryo induction was also improved with the addition of putrescine and spermidine (5, 10, 50, 100, 200, 500, 1000 μM) to the induction medium compared to the control (Table 2).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 87%
“…Results of some of the recent studies also reveal that the replacement of sucrose by maltose enhanced the success of anther culture (Trottier et al 1993). Maltose as a sole carbon source in the culture medium also proved critical for the development of microspore-derived embryos in Triticum aestivum (Mejza et al 1993).…”
Section: Effects Of Other Factors On Anther Culturementioning
confidence: 95%
“…The higher plant regeneration obtained by CHB-2 medium may be due to concentration of the organic nitrogen especially glutamine used in this medium (Mordhorst & lörz, 1993). It has been showed that certain amino acids can be beneficial for embryo maturation and plant regeneration (Trottier et al, 1993). In media without the presence of immature ovaries, cell division was blocked in the developing pathway microspores for embryo formation.…”
Section: The Effect Of Embryo Induction Mediummentioning
confidence: 99%